A BIBLIOMETRIC ANALYSIS OF BOARD DIVERSITY: RESEARCH TRENDS, CHALLENGES, AND FUTURE DIRECTIONS - Christiani, Desi; Widuri, Rindang (Bina Nusantara University, 2024)
Board diversity has become a central issue in corporate governance, with growing recognition of its potential benefits for organizational performance, decision-making, and stakeholder engagement. This paper explores the concept of board diversity, examining various dimensions such as gender, ethnicity, age, and professional background. This study examines the evolution of board diversity, significant trends, and research gaps in current literature through bibliometric analysis. This study employs bibliometric analysis to identify the key areas of research, countries, languages, starting years, top journals, and prolific authors in board diversity. Using (Scopus.Com, n.d.) as the data source, 832 records published between 2016 and 2024 with the keyword